Pengembangan Sumber Daya Manusia (SDM) Dalam Institusi Kepolisian Terhadap Kinerja Anggota Polres Kabupaten Tulungagung - Gohan, Alpho; Daroini, Ahsin (Otonomi, 2025)
The purpose of this research is to know and analyze the impact of structural and technical training, motivation and planning and organization for the performance of police members at the Police Station of the Resor Tulungagung or POLRES Tulungagung in the Tulungagung District. This research uses descriptive quantitative methods. With a population of police officers Tulungagungang with a sample of 90 responders. Data collection method using questionnaire, field observation and literature method. While data analysis uses multiple linear regression analysis. The results of this study show that special training is structural and technical, motivation, planning and organization for member performance. It is supported by the result of r square or coefficient determination (kd ) shows 99.7 % so interpreted if variable x1 (structural and technical), x2 (motivation ) and x3 (planning and organizing capabilities) have a contribution of 99.7 % to variable y (member performance ) and 0.3 % are influenced by other factors other than variable x. In addition, in the f count 189,894 receive is worth of 0,000 sig. Thus showing that the f count greater than f table or 189,894 > 2,71 with the sig 0,000 < 0,05.Thus received hypothesis. While on the outcome of the t known for partial that special training structural and technical, planning and organizing motivation and ability on the performance of members of the police force in POLRES Tulungagung, Tulungagung district